PATHOMORPHOLOGICAL CHANGES IN SALIVARY GLANDS OF RATS UNDER THE CONDITION OF DIABETIC NEUROPATHY AND CORRECTION - Tykhonovych, K.V.; Neporada, K.S.; Yeroshenko, G.A. (World of Medicine and Biology, 2023)
The purpose of the study was to evaluate the effect of diabetic polyneuropathy on the development of pathological changes in the salivary glands of rats, as well as the feasibility of their correction by the drug Cocarnit. Immature white nonlinear rats of both sexes were simulated with streptozocin-induced diabetic neuropathy, which was confirmed by the Randall-Selitto tensoalgometric method. For correction, Cocarnit 1 mg/kg was administered intramuscularly for 9 days. The subjects were the submandibular salivary glands of rats. It was found that streptozocin-induced diabetic neuropathy leads to changes in the parenchymatous components in the lobules of submandibular salivary glands of rats, which was manifested by dystrophic and destructive changes in the epithelial cells of the terminal sections and ducts and blood perfusion in the hemomicrocirculatory vessels. Administration of Cocarnit reduces manifestations of periacinaric edema and improves trophism of epitheliocytes. Restoration of blood flow contributes to the normalization of secretory function of the glandular apparatus of submandibular salivary glands in rats.